Chemical pleurodesis using bleomycin in treatment of patients with transsudative pleural effusion in hepatic failure - A. L. Akopov; A. .. Carlson; S. D. Gorbunkov; A. S. Agishev; A. I. Romanikhin (Вестник хирургии имени И.И. Грекова, 2017)
OBJECTIVE. The authors analyzed the efficacy of bleomycin application as sclerosing agent in patients with transudative pleural effusion in consequence of hepatic failure. MATERIAL AND METHODS. The research included 7 patients with right side hepatic transudative pleural effusion who didn’t respond to conservative medical treatment. Drainage of the right pleural cavity with following injection of bleomycin were performed for all the patients. RESULTS. This procedure was effective in 6 out of 7 patients (86 %). There was a single case of recurrence and lethal outcome (14 %) due to hepatic coma. There weren’t noted any severe side effects during 6 months after induction of bleomycin. CONCLUSIONS. Pleurodesis using bleomycin appeared to be effective and safe method of treatment for patients with hepatic transudative pleural effusions.